2006
DOI: 10.1016/j.bbabio.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling proteins: A role in protection against reactive oxygen species—or not?

Abstract: A physiological function of the original uncoupling protein, UCP1, is well established: UCP1 is the molecular background for nonshivering thermogenesis. The functions of the "novel" UCPs, UCP2 and UCP3, are still not established. Recent discussions imply that all UCPs may play a role in protection against reactive oxygen species (ROS). Here we examine critically the evidence that UCP1, UCP2 and UCP3 are stimulated by ROS (superoxide) or ROS products (4-hydroxy-2-nonenal), and that the UCPs actually diminish ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
111
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 67 publications
1
111
0
5
Order By: Relevance
“…Our studies of UCP expression in nTg mice are consistent with other mammalian studies that show little or no induction of skeletal muscle UCP-3 (35)(36)(37), whereas the induction of UCP-3 in Tg mice is more reflective of what has been observed in the highly oxidative, high-LPL-expressing muscles of birds. The UCP homolog in hummingbirds (hmUCP), with high homology to UCP-1, UCP-2, and UCP-3 (55, 70, and 72%, respectively), is induced in response to the daily bout of torpor and is thought to facilitate the rewarming phase (38).…”
Section: Discussionsupporting
confidence: 79%
“…Our studies of UCP expression in nTg mice are consistent with other mammalian studies that show little or no induction of skeletal muscle UCP-3 (35)(36)(37), whereas the induction of UCP-3 in Tg mice is more reflective of what has been observed in the highly oxidative, high-LPL-expressing muscles of birds. The UCP homolog in hummingbirds (hmUCP), with high homology to UCP-1, UCP-2, and UCP-3 (55, 70, and 72%, respectively), is induced in response to the daily bout of torpor and is thought to facilitate the rewarming phase (38).…”
Section: Discussionsupporting
confidence: 79%
“…4 However, this should not be surprising because the function of UCP1 is quite divergent from UCP2 and UCP3. Indeed, UCP1 serves a thermogenic purpose, and studies have demonstrated that UCP1 does not control ROS levels (48). Moreover, there is evidence that UCP1 can be phosphorylated (49).…”
Section: Discussionmentioning
confidence: 99%
“…UCP1 has also been detected in the thymus where it has the capacity to regulate metabolic flux and the production of reactive oxygen species (ROS) (Carroll et al 2005). The widespread presence of other UCPs in eukaryotes, nonthermogenic animal tissues (mammals, fish, birds and insects), plants and unicellular organisms implies that these proteins may elicit functions other than thermogenesis (for a review, see Cannon et al 2006;Echtay 2007;Jarmuszkiewicz et al 2010;Sluse et al 2006;Nicholls 2006;Vercesi et al 2006). However, the physiological functions of UCP1 homologues are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…UCPs catalyze proton leaking into the matrix and dissipate the proton electrochemical gradient built up during electron transport through the mitochondrial respiratory chain (for a review, see Cannon et al 2006;Echtay 2007;Sluse et al 2006;Nicholls 2006). A direct consequence of the UCP activity stimulated by free fatty acids is a decrease in oxidative phosphorylation efficacy (Skulachev 1996).…”
Section: Introductionmentioning
confidence: 99%